Definition of wear and the technology of processing oil grooves round profil. - Диха, О.В.; Вичавка, А.А.; Дитинюк, В.О. (Problems of Tribology, 2017)
Proposed to approximate the calculated dependence of wear and tear from the way of friction to assess the wear of slide guide with lubrication grooves a round profile at the design stage. The algorithm for calculating the account provides for the choice of optimal parameters of lubricating profile according to the criterion of wear resistance under given operating conditions of the guide. The method of forming shaped oil grooves of variable profile by surface plastic imprint in the surface of the punch.Key words: guide slide, oil profile, calculation of wear, the path of friction, surface-plastic deformation.